A 4-hour Profile of 17-hydroxyprogesterone in Salt-wasting Congenital Adrenal Hyperplasia: Is the Serial Monitoring Strategy Worth the Effort? - Özge Besci; İbrahim Mert Erbaş; Tuncay Küme; Kübra Yüksek Acinikli; Ayhan Abacı; Ece Böber; Korcan Demir (Galenos Yayincilik, 2022)
INTRODUCTION: Objective: Since there is no gold standard laboratory variable for adjustment of treatment in congenital adrenal hyperplasia (CAH), the aim was to assess the use of a 4-hour profile of serum 17-hydroxyprogesterone (17-OHP) to determine the most appropriate sample time and level of 17-OHP in predicting the metabolic control and evaluate the role of sex hormone-binding globulin (SHBG) in hyperandrogenemia. METHODS: Methods: This study included children with salt-wasting CAH. Measurements for 17-OHP and cortisol were made from samples obtained before and 1, 2, and 4 hours after the morning dose of hydrocortisone. Patients were designated to have poor metabolic control when androstenedione levels according to age and sex-specific reference intervals were high and annual height standard deviation score (SDS) changes were ≥0.5. RESULTS: Results: The study cohort was 16 children (9 girls) with a median age of 7-years old. Premedication 17-OHP levels were strongly correlated with 17-OHP levels 1, 2, and 4 hours after the morning dose (rs=0.929, p<0.01; rs=0.943, p<0.01; rs=0.835, p<0.01, respectively). 17-OHP profiles (0, 1, 2, 4 hours) of poor (n=6) and good (n=10) metabolically controlled cases were similar. Among the patients with poor metabolic control, two cases had 17-OHP levels <2 ng/mL at all times. The remaining patients with poor metabolic control had median 17-OHP levels above 104 ng/mL, 82 ng/mL, 14 ng/mL, and 4 ng/mL, for baseline and 1, 2, and 4 hours, respectively. Differences between the poor and well-controlled group were androstenedione levels with respect to upper limit of normal [1.8 (1.5) and 0.5 (1.5) ng/mL, respectively p=0.03], annual change in height SDS [0.7 (0.2) and -0.03 (0.8) SDS, respectively, p=0.001], and daily hydrocortisone doses [7 (6) and 16 (8) mg/m2/day, respectively, p=0.02]. Androstenedione and SHBG levels were negatively correlated in the pubertal children (rs=-0.7, p=0.04). DISCUSSION AND CONCLUSION: Conclusion: We conclude that: (i) a 4-hour 17-OHP profile is not useful in predicting hyperandrogenemia; (ii) suppressed levels of 17-OHP do not always indicate overtreatment; (iii) reference intervals of 17-OHP for different time periods might be of importance; (iv) low hydrocortisone doses should be avoided; and (v) SHBG could be used in pubertal children as an indicator of hyperandrogenemia.